PRODUCTION OF MDP PANELS WITH YERBA MATE HARVEST RESIDUES - PIRES, MARINA APARECIDA; Hillig, Éverton; BEDNARCZUK, EZAQUEL; Mustefaga, Stefani Chagas (Floresta, 2024)
The quality of MDP panels produced with Pinus taeda wood particles mixed with yerba mate harvest residues was evaluated. Monolayer panels were produced with the addition of 0. 20. 40. 60. 80 and 100% proportion of yerba mate waste, with a nominal specific gravity of 0.65 g.cm-³, using 12% urea-formaldehyde resin, 0.5% paraffin and 2% ammonium sulfate catalyst. The panels were pressed for 10 minutes at a temperature of 140°C and pressure of 40 kgf/cm². The physical properties of apparent density, moisture content, water absorption and thickness swelling (2 and 24 hours) were evaluated, as well as the mechanical properties of static bending (MOR and MOE), internal bonding, screw withdrawal on the face and Janka hardness. There was a trend towards an increase in internal bonding with an increase in the proportion of yerba mate residue in the panels, but the opposite occurred for the other mechanical properties studied. Some physical properties such as water absorption and thickness swelling resulted in better performance when yerba mate particles were added. In view of this, it can be concluded that it is possible to produce panels with the addition of yerba mate up to 40% in the composition with yerba mate particles, without affecting the quality of the properties.